Simulação bioeconômica de três modelos de manejo reprodutivo para bovinos de corte - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The aim of present study was to carry out a simulated bioeconomic performance of three systems of reproductive management for beef cattle. For the present simulation, a herd of 1,300 Bos taurus taurus and Bos taurus indicus females (heifers and multiparous cows) were submitted to three different scenarios: 1 - natural mating (MN); 2 - artificial insemination at fixed time (IATF) followed by transfer with bulls; 3 artificial insemination with estrus detection and at fixed time (IAETF) followed by transfer with bulls. Firstly, the compilation of the data of scientific articles involving artificial insemination protocols (IATF and IAETF) and natural selection relative to the percentage of pregnancy obtained in each group for the categories of heifers and multiparous cows. From the compilation of the results already published and the sum of animals and their pregnancies, the weighted mean of pregnancy was 83.7% for the MN group, whereas for the IATF + MN group the weighted mean was 90.1% And for the IAETF + MN group was 91.7%. Considering the percentages obtained in the simulation, losses (8% between embryonic death and abortions and 2.5% post-birth) and costs reached the productive results, which were 171,512.07 (MN), 258,089.62 ( IATF + MN) and 278,616.06 (IAETF + MN) kg of weaned calves. The cost to implement each management in the property was R $ 209,092.00, R $ 168,521.72 and R $ 164,169.17 and gross profit of R $ 785,678.00, R $ 1,328,398.05 and R $ 1,451 .803,94 for MN, IATF + MN and IAETF + MN, respectively. The economic comparison between the MN and IATF groups generated an economic advantage of 40.9% in favor of the IATF, which corresponds to R $ 542,720.05. When compared to MN versus IAETF, the superiority of economic return in favor of the second group was 45.8%, corresponding to R $ 666,125.94. Therefore, both the IATF + MN and the IAETF + MN were useful tools to increase the economic return through the sale of more kg of weaned calves, presenting a substantial increase in the profitability of the beef breeding system.
Bioeconomic simulation of three models of reproductive management for beef cattle
Keywords: IATF; IAETF; Monta natural; Bioeconômica; Bovinos de corte; Reprodução animal; Animal science; CNPQ::CIENCIAS AGRARIAS; Ciência animal